Impact of sarcopenia and frailty on outcomes of patients with sepsis or septic shock: a systematic review and meta-analysis - Ni, Fangchun; Zheng, Lingli (Frontiers in Nutrition, 2025)
BackgroundSarcopenia and frailty are emerging risk factors that may modify outcomes in patients with sepsis or septic shock. This review aims to assess the association of sarcopenia and frailty with mortality, length of stay in the hospital and intensive care unit (ICU), and duration of mechanical ventilation in adults with sepsis.MethodsThe PubMed, EMBASE, Scopus, CINAHL, Web of Science, and CENTRAL databases were searched from inception to May 31, 2025, for observational studies reporting outcomes stratified by sarcopenia and/or frailty in sepsis. Random-effects meta-analyses (Der Simonian–Laird) were done, and the data were presented as pooled odds ratios (OR) for mortality and weighted mean differences (WMD) for continuous outcomes. Cochran’s Q and I2 statistics quantified heterogeneity.ResultsThirty studies (n ≈ 38,000) were included. Sarcopenia (21 cohorts) was associated with higher in-hospital mortality (OR = 1.54; 95% CI: 1.03–2.30; p = 0.034; I2 = 85.5%), longer hospital (WMD = +5.37 days; 95% CI: 2.01–8.73; p = 0.002; I2 = 97.5%), and ICU (WMD = +1.49 days; 95% CI: 0.64–2.34; p = 0.001; I2 = 94.9%) stay and higher duration of mechanical ventilation (WMD = +0.99 days; 95% CI: −0.003 to 1.99; p = 0.051; I2 = 0%). Frailty (9 cohorts) demonstrated a non-significant trend toward increased mortality (OR = 1.68; 95% CI: 0.92–3.05; p = 0.091; I2 = 98.1%) but was linked to more extended ICU stay (WMD = +0.99 days; 95% CI: 0.69–1.28; p < 0.001; I2 = 78.1%). Frailty did not significantly affect hospital length of stay (WMD = –0.44 days; 95% CI: −5.71 to 4.84; p = 0.87; I2 = 99.8%).ConclusionSarcopenia independently predicts worse mortality and prolonged hospitalization in sepsis, underscoring the need for early muscle-preserving interventions. Frailty prolongs ICU stay and may inform shared-decision discussions, although its impact on mortality is less consistent.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251058423, CRD420251058423.